Medical Compliance Determinants for Tuberculosis Patients in Palembang (Jurnal Ilmu Kesehatan Masyarakat, 2020)
The majority of countries in the world have tuberculosis, including Indonesia, which has the third rank in the world. This is due to a large number of sufferers who were not successfully cured. One of the factors that influence the recovery of tuberculosis patients is adherence to taking anti-tuberculosis drugs for a certain period of time. Non-adherence to treatment can exacerbate the risk of disease because it can lead to MDR (Multi Drugs Resistant) tuberculosis. This study aims to analyze the determinants of tuberculosis treatment compliance in the city of Palembang. This study used an analytical study with a semi-quantitative approach, with a cross-sectional design. Sampling was carried out by proportional random sampling at 39 Puskesmas Kota Palembang, a total of 243 samples that met the inclusion and exclusion criteria. Data collection was carried out by means of interviews using a questionnaire. Data were analyzed using the chi-square test and multiple logistic regression. Obtained adherence to treatment of tuberculosis patients by 42.8%. There was a significant relationship between perceived benefits (p = 0.000; OR = 3.556), family support (p = 0.000; OR = 3.512), support from health workers (p = 0.001; OR = 2.712), knowledge (p = 0.018; OR = 2,027) with adherence to treatment of tuberculosis patients. The level of compliance with tuberculosis patients in Palembang City is still low, namely 42.8%. The most important determinant of adherence is perceived benefit with a 3.556 times greater opportunity after controlling for other variables.